Optimizing the Surface Quality of L-PBF Ti6Al4V ELI Alloy via Electropolishing and Its Effect on Corrosion Resistance for Dental Applications - Chatpaiboonwat, Venus; Trachoo, Vorapat; Promoppatum, Patcharapit; Chobaomsup, Viriyah; Saengkiettiyut, Kanokwan; Srimaneepong, Viritpon; Wattanasirmkit, Kamolporn (European Journal of Dentistry, 2025)
The Ti6Al4V ELI alloy produced via laser powder bed fusion (L-PBF) has attracted interest for use in dental applications. However, surface finishing is an important property that can be managed by various methods. The purpose of this study was to investigate the effects of electropolishing (EP) on the surface roughness and corrosion resistance of L-PBF Ti6Al4V ELI alloy.The present study explored the influence of current density (0.3 A/cm2), voltage (15 V), and distance (2 and 4 cm) on the surface quality of L-PBF-printed Ti6Al4V ELI. The potentiodynamic polarization testing was performed to investigate the corrosion behavior of electropolished Ti6Al4V ELI alloy plates.The data variation was compared at different conditions of EP using a one-way analysis of variance and Tukey's post hoc testing at a significance level of 5%.This study showed that EP significantly reduced the surface roughness and enhanced corrosion resistance of printed Ti6Al4V ELI alloy with the best result achieved by using 15 V and 2 cm of anode–cathode distance.This study indicates that customized EP settings are crucial for optimizing the surface properties of Ti6Al4V ELI for use in dental and biomedical applications. However, the corrosion resistance can be reduced due to increased porosity resulting from the EP treatment.
Keywords: corrosion; electropolishing; laser powder bed fusion; surface roughness; Ti6Al4V